Extended air, light, and heat-resistive organolead halide perovskite single-crystalline microrods for high-performance photodetectors. Issue 23 (24th October 2022) - Lin, Chang-Yu; Ulaganathan, Rajesh Kumar; Subramanian, Ambika; Weng, Huei-Chu; Chang, Yaw-Jen; Murugesan, Raghavan Chinnambedu; Sankar, Raman; Rozhin, Alex
Abstract : Two-dimensional organic–inorganic hybrid perovskites are much attracted due to promising stable optoelectronic properties with tunable quantum well structures. Abstract : Two-dimensional organic–inorganic hybrid perovskites are much attracted due to promising stable optoelectronic properties with tunable quantum well structures. Herein, we report the photodetector performance of the structurally tuned FA-incorporated hybrid perovskite FA-(N-MPDA)PbBr4 (FA = formamidinium and N-MPDA = N 1 -methylpropane-1, 3-diammonium) high-quality single-crystalline microrods obtained from over supersaturated solution by a slow evaporation at constant temperature (SECT) growth method. The single crystalline FA-(N-MPDA)PbBr4 microrod exhibits exceptional structural, thermal, and optical stabilities against ambient, light, and heat exposures, which were systematically monitored using X-ray diffraction, photoluminescence, and thermogravimetric analysis/differential scanning calorimetry techniques. The photodetector device fabricated using stable FA-(N-MPDA)PbBr4 crystalline microrod exhibits good responsivity ∼40 A W −1 with a response time of less than 50 ms by shining a 405 nm laser. In addition, the microrods exhibit high specific detectivity of 7.8 × 10 10 Jones at an incident light of 53 μW cm −2 . These results demonstrate the potential of organic–inorganic perovskite microrods formed with a long-chain organic diammonium spacer suitable for stable and high-performance optoelectronic devices.